Asymmetric role of renewable energy, green innovation, and globalization in deriving environmental sustainability: Evidence from top-10 polluted countries. (February 2022) - Sun, Yunpeng; Anwar, Ahsan; Razzaq, Asif; Liang, Xueping; Siddique, Muhammad
Abstract: This study estimates the asymmetric impact of renewable energy consumption, green innovation, globalization, and economic growth on carbon emissions in the top 10 polluted countries from 1991 to 2018. Following the theoretical basis of the STRIPAT model, this study employs a novel estimation technique popularized as Method of Moment Quantile Regression (MMQR). Our preliminary findings strictly reject the assumption of data normality; therefore, it is imperative to employ MMQR, which can efficiently deal with structural changes and non-normality of data. The results from MMQR estimator indicate that globalization contributes to higher carbon emissions across lower, medium, and higher (1st to 9th) quantiles of carbon emissions. Interestingly, the emissions-increasing effect of globalization turns more substantial from lower to higher quantiles. In contrast, renewable energy consumption significantly mitigates carbon emissions mainly at extreme lower (1st to 3rd) and extreme higher (7th to 9th) emissions quantiles. Similarly, green innovations only abate carbon emissions from medium to higher (5th to 9th) quantiles, while lower quantiles possess insignificant effect. The emissions-mitigating effect of both variables is higher at highest quantiles and lower at lowest emissions quantiles. Finally, economic growth and population cause higher emissions across all quantiles. These results suggest pertinent policy recommendations. Highlights: Preliminary findings strictly reject the assumption of data normality. Renewable energy consumption significantly mitigates carbon emissions. Green innovations reduce carbon emissions only at medium to higher quantiles. The emissions-mitigating effect of both variables is higher at the highest quantiles. Globalization contributes to higher carbon emissions across all emission quantiles.